(untitled) (Revista Electrónica Calidad en la Educación Superior, 2022)
Although there are general regulations about plagiarism in academic production and a computer application is used for its detection, there is no consistency in PROMADE regarding decision-making when plagiarism is suspected in teaching material. A qualitative and exploratory research was carried out and a procedure was obtained to make collegial decisions in situations of suspected plagiarism and which consists of four steps: identify the type of materials produced and the percentage of acceptable matches for each one; select the technological tool; parse matches and; finally, apply the Diagram of analysis and decision making on plagiarism. These steps can be adapted to other academic purposes in which teaching material will be produced.